Fortalecimento da autonomia de gestantes e suas repercussões no trabalho de parto e parto - Medeiros, Renata Marien Knupp (2019)
ABSTRACT: The hegemonic obstetric model in Brazil is characterized by a hospital- and medical-centered interventionist assistance, which, over time, has contributed to the expropriation of women's knowledge, control and participation in the parturition process, negatively affecting the birth experience. Among the various investment necessary to interfere with this problem, it is essential to promote the development of greater degrees of autonomy of women, through the joint construction with the participation of both the professional as the woman (co-construction processes), which must be promoted, among various means, by problematizing, critical and counter-hegemonic educational practices, along the reproductive phase and, in particular, in the prenatal period. Considering these aspects, among others, this study aimed to analyze the impact of an educational experience whose specific intent was to subsidize the co-production of autonomy of pregnant women, UHS users, from their participation in this experience, and its impact by means of autonomy expressed by these women during the parturition process. The study is based on the co-production of individuals and collectives of the Paideia method and adopts as a methodological reference the Convergent Care Research, which allows for combining the investigative process to educational activities aimed at transforming the reality studied. The participants were 11 women who attended the educational activity proposal. Data collection used interview techniques, groups of convergence, history of conversations in messages application and participating observation, with records in a field diary. The data were analyzed, as proposed by the referential adopted, through the steps of apprehension, synthesis, theorizing and transfer. As a result of the educational experience, there was the expansion of the network of social support of pregnant women who sought, in mutual support, the strengthening of individual trust for the delivery experience; the re-elaboration of understandings about labor and delivery, which began to be understood as a natural and physiological process; the strengthening of personal resources/skills from the confidence in their own body; the recognition of women as subjects with rights; the elaboration of conscious choices and coresponsibility with their own health, expressed by a more active involvement with the gravidpuerperal process. The main barriers to the expression of the autonomy of women, identified in the parturition process, were: doctor-patient relationship of conflict, intense painful sensation and the presence of unprepared companions. In the same way, the woman's autonomy was favored by the warm and respectful interaction with professionals and the presence of the delivery plan. Satisfaction with the delivery was directly related to the protagonism lived in the parturition process. The positive experiences of participants and the significant results of autonomy expressed by them in this study indicate the potential of activities of this nature, which must be improved and reproduced. Therefore, for the subject's exercise of autonomy, in addition to its strengthening, there is a need for greater democratization of institutions.